On representations of the group of order two over local factorial rings in the weakly modular case - Bondarenko, V.M.; Stoika, M. (Algebra and Discrete Mathematics, 2017)
We study representations of the group of order 2 over local factorial rings of characteristic not 2 with residue field of characteristic 2. The main results are related to a sufficient condition of wildness of groups.